A foreign affair [videorecording (DVD)] - Wilder, Billy, 1906-2002; Arthur, Jean, 1900-1991; Dietrich, Marlene; Lund, John, 1911-1992; Mitchell, Millard, 1900-1953 (TCM vault collection., 2013)
"Phoebe Frost, an upright Republican member of Congress, travels to Berlin to look into reports of corruption among the occupying American forces. She enlists an Army captain in her crusade and finds herself falling for him, unaware that he is the man romantically involved with a German cabaret singer who can lead army investigators to a high-level Nazi war criminal"--Container.